2017
DOI: 10.22271/tpr.2017.v4.i3.059
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of a fly ash and root-knot nematode pathogens on Pumpkin (Cucurbita moschata Duch. ex Lam.)

Abstract: Abstract:In the present investigation it was tried to find out the interactive effect of various level of fly ash (abiotic) and root-knot nematode, Meloidogyne incognita (biotic) on plant growth, yield and some biochemical contents in pumpkin (Cucurbita moschata). The experiments were conducted in pots with different level of fly ash and soil mixture in the green house at Department of Botany, Aligarh Muslim University, Aligarh, India. Seeds of pumpkin (F1 hybrid-Nutan) were grown in pots filled with different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…Therefore, higher levels of FA adversely affect the growth, yield and pigment content of Indian mustard. Similar results have been observed on several crops such as wheat [8], potato [23] and pumpkin [1]. In the present study, the 30% FA was found best which shows that available nutrients in FA are beneficial at certain levels for utilization of a specific plant species.…”
Section: Chlorophyll Contentsupporting
confidence: 90%
See 1 more Smart Citation
“…Therefore, higher levels of FA adversely affect the growth, yield and pigment content of Indian mustard. Similar results have been observed on several crops such as wheat [8], potato [23] and pumpkin [1]. In the present study, the 30% FA was found best which shows that available nutrients in FA are beneficial at certain levels for utilization of a specific plant species.…”
Section: Chlorophyll Contentsupporting
confidence: 90%
“…The improvement in chlorophyll content could be due to the presence of Mg in FA, which is the main component of chlorophyll and is required for the structural integrity of chloroplast. The beneficial effect of FA at lower levels (10-30%) has already been observed on many crops such as tomato [15], wheat [8], chickpea [9], potato [23], pumpkin [1].…”
Section: Chlorophyll Contentmentioning
confidence: 99%
“…In the present investigation, chili plant growth and production increased significantly at the lower levels of fly ash (T6 = 10% FA + 2 g T. harzianum + 2000J2 of M. incognita). There have been similar beneficial effects on various crops such as pumpkins and carrots (Ahmad et al, 2017;Haris et al, 2019). Due to its high K, Mg, and S content, fly ash is a valuable source of essential plant nutrients and is used as fertilizer to boost crop growth (Ahmed et al, 2021a).…”
Section: Discussionmentioning
confidence: 95%
“…This reaction of Fayrouz may be due to it carrying Mi-1.1 and Mi-1.2 genes (Heikal et al 2008). Therefore, as a result of an irregular supply of water, nutrients, photosynthates and energy, the growth and development of leaf tissue and its constituents especially chlorophyll pigments are severely affected (Khan and Khan 1997;Strajnar et al 2012;Ahmad et al 2017). These effects were clearly seen on all susceptible genotypes compared to resistant genotypes.…”
Section: Discussionmentioning
confidence: 99%